KEDUDUKAN FIDUCIA SEBAGAI SUATU LEMBAGA JAMINAN DALAM PERFEKTIF UNDANG-UNDANG NOMOR 42 TAHUN 1999 TENTANG FIDUCIA - Prawitra Thalib (Jurnal LEX SPECIALIS, 2010)
Trade is becoming the more important activity in this era, because the vital foundation of economic aspect is a trade, but to realize that sometimes is more fund or capital is needed to expand trade limit, that not was an easy task because fund not come so freely it will take some refund from debitor to creditor in this situation fiducia will be the best choice of that, because is not take hard and long procedure and the guarantee still at creditor hand, so the creditor can used to expand his trade activity, but thats not the problem because the right issue is how can a goverment to make sure that process will be succes and dont jeopadize each subject, Act No 42 Year 1999 about Fiducia is established to resolve that issue to regulating the process of fiducia to help someone who need more fund with easy refund. Key Note : Fiducia in persfective of Act No 42 Year 1999